2002
DOI: 10.1002/ajh.10149
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia and the MTHFR C677T mutation in Budd‐Chiari syndrome

Abstract: Hyperhomocysteinemia (HH) is a factor that predisposes individuals to thrombosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 30 publications
4
40
1
Order By: Relevance
“…A recent study from Northern India 29 demonstrated the importance of an interaction between genetic and acquired risk factors in HVT, but in contrast to our findings, FVL was found to be the most common (17%) inherited risk factor. Our findings are compatible with those of a Chinese study 30 suggesting that both genetic hemochromatosis and the homozygous C677T mutation in the MTHFR gene are important risk factors for HVT.…”
Section: Mesenteric Vein Thrombosissupporting
confidence: 92%
“…A recent study from Northern India 29 demonstrated the importance of an interaction between genetic and acquired risk factors in HVT, but in contrast to our findings, FVL was found to be the most common (17%) inherited risk factor. Our findings are compatible with those of a Chinese study 30 suggesting that both genetic hemochromatosis and the homozygous C677T mutation in the MTHFR gene are important risk factors for HVT.…”
Section: Mesenteric Vein Thrombosissupporting
confidence: 92%
“…Prevalence of heterozygote MTHFR gene mutation in patients with venous thrombosis is similar to healthy controls suggesting that this mutation is not an important prothrombotic factor [24] . It has been shown that homozygote MTHFR mutation, one of the causes of hyperhomocystinaemia (risk factor for vascular disease), is a risk factor for venous thrombosis [19,24] . None of the patients in the present study were homozygous for the MTHFR mutation.…”
Section: Discussionmentioning
confidence: 70%
“…36 Homocysteine is often elevated due to a vitamin deficiency (vitamin B12, vitamin B6 and folate), chronic disease (chronic liver disease, chronic kidney disease, hypothyroidism) or due to a genetic variant in the methylenetetrahydrofolate reductase (MTHFR). The MTHFR mutation has been found to increase the risk of BCS; 37 the exact prevalence of hyperhomocysteinemia is difficult to assess in BCS because homocysteine is often increased during chronic liver disease. 38 Oral contraceptive use is a frequent risk factor for BCS.…”
Section: Myeloproliferative Neoplasia (Mpn)mentioning
confidence: 99%